Activated carbon from oil palm mesocarp fiber for the treatment of final discharge of palm oil effluent - Ibrahim, Izzudin (2016)
Malaysia palm oil industry produced abundant amounts of solid and liquid biomass annually. The current disposal practice is not environmentally friendly, with viable biomass for production of value added product being wasted. It is desirable to reuse the biomass as a feedstock for production of activated carbon and use it to treat palm oil mill final discharge to achieve zero emission system. This study aimed to reduce the COD and suspended solids content of palm oil mill final discharge using oil palm mesocarp fiber activated by steam and phosphoric acid. The oil palm mesocarp fiber activated carbon was successfully produced either using steam and phosphoric acid as activating agents in a two-step process at a temperature of 600°C for 30 minutes. The resulting activated carbon BET surface area was found to be 494 and 1090 m2/g, respectively, which are comparable to commercial activated carbon. The activated carbon also shows pore development compared to raw material from SEM analysis. Oil palm mesocarp fiber activated carbon was used to treat palm oil mill final discharge and the effect of adsorbent dosage, treatment time, adsorbate concentration and consecutive treatments was studied. The oil palm mesocarp fiber activated carbon were able to reduce the COD and suspended solids content of the final discharge with a COD percent removal of 70% and 42 % for phosphoric acid and steam activated mesocarp fiber at 10 g/L dosage, respectively. For suspended solids, the removal percent was 85% and 81%, respectively. The amount of pollutant reduced increased as the adsorbent dosage increase and remained constant after 10 g/L. In terms of treatment time, as the treatment time increased, the amount of pollutants that were removed increased until a certain amount of time, which was found to be 6 hours for both COD and suspended solids content. For adsorbate concentration, as the COD initial concentration increased, reduction of pollutants for phosphoric acid activated carbon maintained, while steam activated carbon shows a higher reduction at lower concentration. For suspended solids, a similar effect was observed. The effect of consecutive treatment was also studied, with the increasing number of treatments resulting in a higher total reduction of pollutants. Consecutive small dosage treatment also proves to be more efficient compared to a single large dosage treatment. It can be concluded that oil palm mesocarp fiber is a viable feedstock for activated carbon production, with resulting activated carbon able to reduce the pollutants in palm oil mill final discharge.